Humanism Enhancing Student Motivation in History Learning Through AI-Driven e-Cooperative and e-Collaborative Methods in Rural Education - Ni, Lee Bih; Shin, Connie (RIRAI Publisher, 2025)
This research explores the influence of AI-based e-cooperative and e-collaborative approaches on boosting student motivation in history education in rural areas. Through the integration of primary data obtained from student surveys and teacher interviews, quantitative indicators of academic achievement, and qualitative insights from case studies, the study emphasizes how AI-driven platforms customize learning experiences, encourage peer collaboration, and enhance engagement. Results show that collaboration enhanced by AI boosts participation levels, enhances historical awareness, and fosters a sense of togetherness among students in distant regions. The research highlights the ability of AI to revolutionize history education by enhancing interactivity, accessibility, and engagement for students in disadvantaged rural areas.